The Ethics of Citizen Science and Knowledge Games: Five Emerging Questions About Games that Support Citizen Science - Schrier, Karen Kat (Gamevironments, 2021)
Citizen science games such as Foldit (2008), EteRNA (2010), Eyewire (2012), and StallCatchers (2016) have been increasingly used to produce new knowledge. These games rely on the participation of the public - often amateurs or nonscientists - to help solve large-scale problems by contributing and analyzing information through a game. We can call these games knowledge games, as they enable researchers and the public to work together to produce new knowledge. However, there has been little attention to the ethical and social implications of knowledge games, possibly because they constitute a small proportion of both games and citizen science activity and because their goals are societally beneficial, e.g., cure cancer, halt Alzheimer's disease. The purpose of this article is to explore and deliberate the ethical complexities of knowledge games. Five key areas of concern emerged from a literature review of related domains: data (How is data collected, managed, analyzed, manipulated, and used?), the game's context (How does using a game affect knowledge production?), accessibility (Is the game accessible and equitable in participation?), participation dynamics (How are players valued?), and design (How are ethics embedded in the game's design and what is the impact?). Recommendations and next steps are discussed.